Drivers of Structural Transformation: The Case of the Manufacturing Sector in Africa. (November 2017) - Mijiyawa, Abdoul' Ganiou
Highlights: There is a U-shaped relationship between the manufacturing share of GDP and per capita GDP in Africa. Good governance, especially a low level of corruption and better government effectiveness contribute to Africa's manufacturing development. Exchange rate depreciation stimulates Africa's manufacturing sector. The size of domestic market matters for manufacturing development in Africa. Abstract: This paper analyzes the driving factors of manufacturing development in Africa. Using the system-GMM technique with four-year average panel data over the period 1995–2014, including 53 African countries, the paper finds four main results. (1) There is a U-shaped relationship between the manufacturing share of GDP and per capita GDP. (2) Exchange rate depreciation stimulates Africa's manufacturing sector. (3) Good governance, especially a low level of corruption and better government effectiveness contribute to Africa's manufacturing development. (4) The size of domestic market positively affects the manufacturing share of GDP. On the other hand, the paper finds no significant effects of FDI and urbanization on manufacturing development. The implication of these findings is that improving the level of competitiveness, expanding the size of domestic market, combating corruption as well as improving government effectiveness are key for Africa's manufacturing sector development. Moreover, the U-shaped relationship between the manufacturing share of GDP and per capita GDP, implies that African countries should not expect industrialization to automatically happen with income increase, but rather, they should proactively tackle key obstacles to the development of the manufacturing sector.